2019
DOI: 10.1177/0047287519830789
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Place Attachment, Ad-Evoked Positive Affect, and Motivation on Intention to Visit: Imagination Proclivity as a Moderator

Abstract: Integrating the theoretical foundations of symbolic interactionism, parasocial interaction, direct affect transfer, push and pull motivational framework, and narrative transportation, this study investigates the determinants of tourists’ intention to visit a destination using Heidi, a famous literary and television series persona, as a stimulus. Place attachment, ad-evoked positive affect, and motivation were theorized as antecedents of intention to visit and imagination proclivity as a moderator. The model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(76 citation statements)
references
References 164 publications
(296 reference statements)
5
69
0
2
Order By: Relevance
“…Blumer's (1969) symbolic interaction theory posited that individuals' behavior is driven by symbolic meanings acquired through interaction with significant others, which could include personalities on mass media. (Hosany, Buzova, and Sanz-Blas 2020). In the online domain, social media platform users may be motivated to perform a particular action (e.g., the impetus to visit/ avoid) toward the mediated object (e.g., a featured place) based on the meaning acquired by interaction or observation of prominent accounts.…”
Section: Future Research Recommendationsmentioning
confidence: 99%
“…Blumer's (1969) symbolic interaction theory posited that individuals' behavior is driven by symbolic meanings acquired through interaction with significant others, which could include personalities on mass media. (Hosany, Buzova, and Sanz-Blas 2020). In the online domain, social media platform users may be motivated to perform a particular action (e.g., the impetus to visit/ avoid) toward the mediated object (e.g., a featured place) based on the meaning acquired by interaction or observation of prominent accounts.…”
Section: Future Research Recommendationsmentioning
confidence: 99%
“…A plausible reason for this discrepancy may be the dominance of behavioral rather than cognitive psychology in previous studies on tourism experiences (Skavronskaya et al, 2017a,b). Studies have found that emotions are related to increased memorability of a tourism experiences (Bastiaansen et al, 2019;Hosany et al, 2019), but do not provide adequate insights into the theoretical mechanisms by which these concepts are connected (Scott, 2020). Cognitive psychology is the field that examines the mechanisms by which our brain experiences and interprets external stimuli and provides insights into the mental processes connecting perception of stimuli with behavior (Neisser, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Table 3.3 and 3.4, above show that the explanations in the two questions come from different studies on popular culture and tourism motivation. The various push factors and pull factor variables came from the articles of different researchers (Busby et al, 2013;Chang, 2016;Gjorgievski & Melles Trpkova, 2012;Güzel & Güzel, 2017;Hosany et al, 2020;Josiam et al, 2020;Michael et al, 2020;Ng & Chan, 2020;Oviedo-García et al, 2016;Suni & Komppula, 2012). These questions were also used Likert scale ranging from 1very important to 7-very unimportant.…”
Section: Structurementioning
confidence: 99%